Brain ventriculomegaly in Down syndrome mice is caused by Pcp4 dose-dependent cilia dysfunction. (9th January 2017) - Raveau, Matthieu; Nakahari, Takashi; Asada, Sachie; Ishihara, Keiichi; Amano, Kenji; Shimohata, Atsushi; Sago, Haruhiko; Yamakawa, Kazuhiro
Abstract: Down syndrome is a leading cause of congenital intellectual disability caused by an additional copy of the chromosome 21. Patients display physiological and morphological changes affecting the brain and its function. Previously we showed that Ts1Cje and Ts2Cje, Down syndrome mouse models carrying overlapping trisomic segments of different length, show similar ventriculomegaly and neurogenesis dysfunction leading to the hypothesis of a cause-consequence relationship between these phenotypes. However, we here discovered that Ts1Rhr Down syndrome model, carrying an even shorter trisomic segment, was sufficient to trigger ventricular enlargement and ependymal cilia beating deficiency without affecting neurogenesis. We further found that Pcp4 gene on the Ts1Rhr trisomic segment is expressed in ependymal cells, and its resumption to two copies rescued both ventricular enlargement and cilia dysfunction in Ts1Rhr mice. This work underlines a Pcp4 -dependent ciliopathy in Down syndrome brain affecting cerebrospinal fluid flow.